Fracture analysis on involute spline of large tunnel boring machine - Bian, Xinxiao; Liu, Yuanrong; Zhang, Jitao (Engineering failure analysis, 2022)
•This paper reports an unpublished failure phenomenon of spline shaft, that is, the tooth root failure on the non working side is more serious than that on the working side, and the crack on the non working side is wider and longer than that on the working side.•This phenomenon is contrary to our conventional understanding about gear fracture.•The gear breaks from the working side tooth root.•Through microscopic analysis, theoretical calculation and simulation test, this failure belongs to the torsional fracture. The main drive spline shafts of two large tunnel boring machines were broken after service of less than 150 h. The failure located at the section flush with the end of the spline sleeve. Different from the gear fracture occurred at the tooth roots of the working side, the spline fracture started from the tooth roots of the non-working side. The non-working side cracks were wider and longer than these of working side, and their damage were more serious. At the failed roots, there were obvious fan-shaped shellfish lines which these were significant fatigue characteristics. Through chemical composition test and metallographic analysis, the spline shaft material was speculated to be 17CrNiMo6, and quenched and tempered heat treatment. The microstructure was mainly bainite with tempered martensite and retained austenite. The micro-hardness was uneven and fluctuated between 31 and 43HRC. Sulfide inclusion was grade 2 and alumina inclusion was 2.5. The calculation by finite element method (FEM) showed that the maximum stress was located at the tooth root of the non-working side. The safety factors calculated by three methods were less than 1.0. Therefore, the root cause of spline failure is improper design and heat treatment. Failure analysis, theoretical calculation and simulation test show that the failure mode was torsion fracture.